Baby's first felony - Straley, John, 1953- (A Cecil Younger investigation, 2018)
"Shamus Award-winner and critical darling John Straley returns to his beloved Cecil Younger series, set in Sitka, Alaska. Criminal defense investigator Cecil Younger spends his days coaching felons on how to avoid incriminating themselves. He and his colleague have even started writing a helpful handbook with tips such as: Don't wear the tennis shoes you stole to court when the guy you stole them from will be there to testify and his name is still written inside of them. But when Cecil follows a lead from a defendant and walks out of a shady apartment complex with a suitcase containing fifty thousand dollars in cash, he suddenly finds himself in violation of one of his own rules: Nothing good comes of walking around with a lot of someone else's money. And the suitcase is only the beginning. Delivered in the form of a statement to a panel of three judges, we find a reluctant, deeply unlucky investigator who, in a single day, manages to find a deep freeze full of drug-stuffed fish, witness a murder at close range, and have his teenage daughter kidnapped and held as collateral"--